UPAYA MENINGKATKAN KETEPATAN PENGGUNAAN KATA GANTI ORANG DALAM MENULIS PUISI MELALUI MEDIA KARTU KATA PADA SISWA KELAS X1 SMA NEGERI 2 JEMBER - Rifdah Adilah Achsani; Yerry Mijianti; Rini Istifadah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low accuracy of the use of personal pronouns in writing poetry by students, even though this element has an important role in building meaning, atmosphere, and emotional closeness in literary works. The purpose of this research is to improve the accuracy of the use of personal pronouns in writing poetry texts through the use of word cards media in Indonesian language learning. The method used is classroom action research with a qualitative and quantitative approach implemented in two cycles. Data were obtained through observation, tests, and documentation. The results of the study showed an increase in students' abilities both qualitatively and quantitatively. Qualitatively, students experienced an increase in creativity, activeness, and understanding in using personal pronouns in poetry. Quantitatively, students' average score increased from 50 in cycle I to 77 in cycle II. In addition, the use of word cards media has proven effective in increasing learning motivation, cooperation, and other language skills. Thus, word cards media can be an appropriate alternative in improving students' poetry writing skills, especially in the use of personal pronouns correctly.